5(1-2(2z-1))=-3(3z-1)+1

Simple and best practice solution for 5(1-2(2z-1))=-3(3z-1)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(1-2(2z-1))=-3(3z-1)+1 equation:


Simplifying
5(1 + -2(2z + -1)) = -3(3z + -1) + 1

Reorder the terms:
5(1 + -2(-1 + 2z)) = -3(3z + -1) + 1
5(1 + (-1 * -2 + 2z * -2)) = -3(3z + -1) + 1
5(1 + (2 + -4z)) = -3(3z + -1) + 1

Combine like terms: 1 + 2 = 3
5(3 + -4z) = -3(3z + -1) + 1
(3 * 5 + -4z * 5) = -3(3z + -1) + 1
(15 + -20z) = -3(3z + -1) + 1

Reorder the terms:
15 + -20z = -3(-1 + 3z) + 1
15 + -20z = (-1 * -3 + 3z * -3) + 1
15 + -20z = (3 + -9z) + 1

Reorder the terms:
15 + -20z = 3 + 1 + -9z

Combine like terms: 3 + 1 = 4
15 + -20z = 4 + -9z

Solving
15 + -20z = 4 + -9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '9z' to each side of the equation.
15 + -20z + 9z = 4 + -9z + 9z

Combine like terms: -20z + 9z = -11z
15 + -11z = 4 + -9z + 9z

Combine like terms: -9z + 9z = 0
15 + -11z = 4 + 0
15 + -11z = 4

Add '-15' to each side of the equation.
15 + -15 + -11z = 4 + -15

Combine like terms: 15 + -15 = 0
0 + -11z = 4 + -15
-11z = 4 + -15

Combine like terms: 4 + -15 = -11
-11z = -11

Divide each side by '-11'.
z = 1

Simplifying
z = 1

See similar equations:

| -5.6(3x+5)-1.8(4x-6)= | | 0.02(6t-7)=0.12(t+1)-0.26 | | 3(7n-2)+8n= | | 3x^3-5x-2=0 | | 4-1+7=5x+6 | | 46-50x=88y | | 4m^3-6m^2-4m=0 | | 6r+5r= | | Y=-2.3+4x | | 15x+50y=1320 | | -6-6=4x | | 3x-4y+2z=-3 | | 3y+47y+z= | | c^2=5c+84 | | 5+4z= | | x+48+42=180 | | x+121=180 | | x+48+11=180 | | 3-3x=6-4-5 | | (x+35)+(x+95)=180 | | x+126=180 | | x+30+24=180 | | 9y^2-18x+33y-60= | | -15+x=180 | | X=8m^2-24m | | -8x^2+72=6x^3-54x | | x+135+60=180 | | -5.6(4y+6)-2.5(2y-4)= | | 7x^2+7x+3= | | 24x+6y=120 | | g(x)=log(x-1) | | (28b-4)-9(3b+4)=-6 |

Equations solver categories